(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
Administration of drugs through skin has received great attention through the last decade. Hence this study aims to formulate an anti-histaminic drug-Chlorpheniramine maleate (CPM) as transdermal patch using different bioadhesive polymers such as ethyl cellulose, cellulose acetate, and polyvinyl pyrrolidon with different plasticizers such as propylene glycol (PG) and polyethylene glycol 400 (PEG400). Patches were prepared though solvent evaporation method, evaluated for their physical and mechanical properties and then subjected to stability study to select the best formulae to be evaluated in vitro and in vivo. The selected formulae were examined for CPM release in phosphate buffer saline pH 5.5 and also tested for CPM permeation through ear rabbit skin. Finally, one formula was evaluated in vivo in comparison with multiple oral doses of commercial CPM oral tablets and results showed that CPM transdermal patch has higher bioavailability than an oral tablet of the same dose, with lower plasma fluctuation and less administration frequency. Key words: Transdermal patch, chlorpheniramine maleate, polymers, bioadhesive